PsycEXTRA Dataset 2000
DOI: 10.1037/e441302008-001
|View full text |Cite
|
Sign up to set email alerts
|

A review of the literature on the effects of low doses of alcohol on driving-related skills

Abstract: A review of the scientific literature regarding the effects of alcohol on driving-related skills was conducted. One hundred and twelve articles -from 1981 to 1997 -were reviewed. Results were indexed by BAC and behavioral area and entered into a database. Two separate analyses were conducted. The first analysis determined the lowest BAC at which impairment is reliably present in driving-related skills. The second analysis determined the thresholds of impairment for each of twelve separate behavioral areas. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
161
0
11

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(187 citation statements)
references
References 98 publications
13
161
0
11
Order By: Relevance
“…Research has shown that alcohol impairs driving skills and increases crash risk [1]. Within the European Union, average yearly road traffic accidents between 1991 and 1998 involved 10,000 (21.3%), out of the 47,000 fatal accidents, related to alcohol [2].…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that alcohol impairs driving skills and increases crash risk [1]. Within the European Union, average yearly road traffic accidents between 1991 and 1998 involved 10,000 (21.3%), out of the 47,000 fatal accidents, related to alcohol [2].…”
Section: Introductionmentioning
confidence: 99%
“…Psychomotor, set-shifting, and working memory functions were investigated. These cognitive domains have previously demonstrated sensitivity to BrACs as low as 20 mg/dl (for a review, see Moskowitz & Fiorentino, 2000).…”
mentioning
confidence: 99%
“…Popularnosti vremena reakcije doprinelo je i to što je pod uticajem raznovrsnih či-nilaca, koji nisu karakteristike prikazivanih stimulusa, već različitih trenutnih i/ili trajnih individualnih obeležja. Tako ono varira u zavisnosti od, na primer, starosti ispitanika, pola, uzbuđenja, konzumiranja alkohola, osobina ličnosti, anksioznosti i sličnog (Der & Deary, 2006;MacDonald, Nyberg, Sandblom, Fischer, & Backman, 2008;Moskowitz & Fiorentino, 2000;Robinson & Tamir, 2005;Welford, 1977). Zahvaljujući ovome upotreba vremena reakcije se iz kognitivne psihologije proši-rila i na ostale oblasti psihologije.…”
Section: Analiza Vremena Reakcije Modelovanjem Linearnih Mešovitih Efunclassified